The Levant in Transition: No. 4 - Parr, P.J., author.
1 online resource (128 pages)
Keywords: The latter part of the 3rd millennium BC witnessed severe dislocations in the social, economic and political structures of the lands at the eastern end of the Mediterranean Sea - the Levant. In the south, in what is now Israel, the Palestinian Territories and Jordan, hitherto thriving urban centres disappeared, to be replaced for several centuries.